2013
DOI: 10.5897/jat2013.0106
|View full text |Cite
|
Sign up to set email alerts
|

Earnings management and performance of French IPO companies

Abstract: In this paper, we examine the impact of discretionary current accruals on the performance of French IPO companies. We first note income-increasing earnings management in the first year as a public company and not in the year before the IPO (Initial Public Offerings). Based on a sample of 139 French IPOs over the period 1999 to 2007, including 38 failures, we also document that companies associated with aggressive earnings management in the IPO process, tend to suffer from subsequently poor returns and to delis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 97 publications
3
17
0
1
Order By: Relevance
“…Using multivariate regression analysis, the results showed a significant positive association between conservative accounting and the quality of financial reporting. Chiraz and Anis (2013) examines the impact of earnings management on the performance of the IPO on the Paris Stock Exchange. Corporate performance is measured on the basis of the ROA, MV, and EPS.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Using multivariate regression analysis, the results showed a significant positive association between conservative accounting and the quality of financial reporting. Chiraz and Anis (2013) examines the impact of earnings management on the performance of the IPO on the Paris Stock Exchange. Corporate performance is measured on the basis of the ROA, MV, and EPS.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…However, there are studies which criticize conservatism for the potential distortion of information, its negative impacts on resource allocation and on corporate performance. While the relationship between performance and accounting conservatism has been the theme of intensive research in developed and developing economies, for example Ugwunta and Ugwuany (2019) in Nigeria, Sana'a (2016) in Jordan, Chiraz and Anis (2013) in France, Chiraz and Anis (2013) in Iran, and Chan et al (2006) in the UK, no such studies have been conducted in Egypt. According to the contingency theory, the relationship between conservative accounting and corporate performance differs according to the diverse institutional environment.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Lin and Tian (2012) presents the negative association between accounting conservatism and underpricing of initial public offerings especially when information asymmetry is high in the Chinese stock market between the years 2001 and 2009. Chiraz and Anis (2013) find no evidence to verify the relation initial proceeds and discretionary current accruals in 139 French IPO firms 1999 to 2007. However, they also concluded that first year for the firms as a public company is the highest period for earnings inflation.…”
Section: Initial Public Offerings In Turkeymentioning
confidence: 89%
“…Therefore, managers of younger and less experienced firms have stronger incentives to manage earnings to increase them (Chiraz and Anis, 2013).…”
Section: Control Variablesmentioning
confidence: 99%
“…We also include the firm age variable (YEARS), as the literature points out the important effect of age of company and earnings management (Anthony and Ramesh, 1992;Petersen and Rajan, 1997;Liu, 2006;Fan, 2007;Stubben, 2010;Lee and Masulis, 2011;Chiraz and Anis , 2013). A firm's age has an impact on executives' decision-making process and how they manage different situations.…”
Section: Yearsmentioning
confidence: 99%